A review of the cellar spider genus Psilochorus Simon 1893 in America north of Mexico (Araneae: Pholcidae) - Slowik, Jozef (Zootaxa, 2009)
The genus Psilochorus Simon, 1893 is reviewed for America north of Mexico. Nineteen species, five of which are new, are described, illustrated, mapped, and a key is provided for identification. Species included are: P. acantus Chamberlin and Ivie, 1942; P. apicalis Banks, 1921 (=P. gertschi Schenkel, 1950, new synonym); P. bantus Chamberlin and Ivie, 1942; P. californiae Chamberlin, 1919; P. coloradensis new species; P. concolor new species; P. hesperus Gertsch and Ivie, 1936; P. hooki new species; P. imitatus Gertsch and Mulaik, 1940; P. inyo new species; P. pallidulus Gertsch, 1935 (= P. coahuilanus Gertsch and Davis, 1937, new synonym); P. papago Gertsch and Davis, 1942; P. pullulus (Hentz, 1850); P. redemptus Gertsch and Mulaik, 1940; P. rockefelleri Gertsch, 1935; P. simoni (Berland, 1911) (= P. simplicior Chamberlin and Ivie, 1942, new synonym); P. topanga Chamberlin and Ivie, 1942; P. texanus new species; P. utahensis Chamberlin, 1919. Information on P. cornutus (Keyserling, 1887) is examined and the species is declared nomen dubium.